Analysis of Hospital Discharge Data to Characterize Obstructive Sleep Apnea and Its Management in Adult Patients Hospitalized in Canada: 2006 to 2007 - Kathy F Spurr; Debra L Morrison; Michael A Graven; Adam Webber; Robert W Gilbert (Canadian Respiratory Journal)
BACKGROUND: Diagnosed obstructive sleep apnea (OSA) affects 2% to 7% of middle-age persons worldwide and represents a substantial health care burden. The gold standard for treating OSA in adults is continuous positive airway pressure (CPAP) therapy. Compliance with this treatment is especially important in OSA patients experiencing concomitant acute and chronic disease or illness, and those undergoing procedures associated with sedation, analgesia and anesthesia.